PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN NASABAH PADA PT. BANK RAKYAT INDONESIA (PERSERO) TBK. KANTOR UNIT OESAPA - Maria Assumpta De Araujo; Soni letek; Yohanes Soares (Mount Hope Management International Journal, 2024)
The formulation of the problem in this study is "Is Quality of Service influenced on customer satisfaction at PT. Bank Rakyat Indonesia (Persero), Tbk. The data analysis technique used in this research is statistical analysis with simple linear regression technique using the application SPSS version 22, Oesapa Office Branch of Kupang Unit of 30.124 people in 2021. Based on the results of the analysis of the impact of service quality on customer satisfaction of PT. Bank Rakyat Indonesia (Persero), Tbk. Office Unit Oesapa, known value a or constant value of 2,368 shows that when the quality of service is 0 then the customer’s satisfaction is 2,368, using the regression equation is Y2,368+0,520X. Whereas the value b as a regression coefficient of 0,520 indicates that service quality has a positive influence on client satisfaction. This means that if the quality of service increases by 1% then customer satisfaction will also increase by 0.520 or 52%. Therefore, management should make the best possible effort to continue to improve the quality of services in order to increase customer satisfaction of BRI Branch Kupang